The S1P2 receptor regulates blood-brain barrier integrity and leukocyte extravasation with implications for neurodegenerative disease. (June 2021) - Xiang, Ping; Chew, Wee Siong; Seow, Wei Lun; Lam, Brenda Wan Shing; Ong, Wei-Yi; Herr, Deron R.
Abstract: Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid which modulates vascular integrity through its receptors, S1P1 –S1P5 . Notably, S1P2 has been shown to mediate the disruption of cerebrovascular integrity in vitro and in vivo . However, the mechanism underlying this process has not been fully elucidated. We evaluated the role of S1P2 in blood-brain barrier (BBB) disruption induced by lipopolysaccharide (LPS)-mediated systemic inflammation and found that BBB disruption and neutrophil infiltration were significantly attenuated in S1pr2 −/− mice relative to S1pr2 +/− littermates. This is concomitant with attenuation of LPS-induced transcriptional activation of IL-6 and downregulation of occludin. Furthermore, S1pr2 −/− mice had significantly reduced expression of genes essential for neutrophil infiltration: Sele, Cxcl1, and Cxcl2 . Conversely, pharmacological agonism of S1P2 induced transcriptional activation of E-selectin in vitro and in vivo . Although S1P2 does not appear to be required for activation of microglia, stimulation of microglial cells with the S1P2 potentiated the response of endothelial cells to LPS. These results demonstrate that S1P2 promotes LPS-induced neutrophil extravasation by inducing expression of endothelial adhesion molecule gene, Sele, and potentiating microglial inflammation of endothelial cells. It is likely that S1P2 is a mediator of cerebrovascular inflammation and represents a potential therapeutic target for neurodegenerative disease such as vascular cognitive impairment. Graphical abstract: Image 1 Highlights: Blood-brain barrier (BBB) disruption is a hallmark of Alzheimer's disease (AD). Processes that regulate BBB integrity are incompletely characterized. There are no known interventions to improve BBB function in AD. S1P2 mediates inflammatory loss of BBB integrity and leukocyte infiltration. This is likely due to induction of E-selectin and chemokines in endothelial cells.